Metastatic Breast Cancer to the Bladder - Salari, MD, Bijan; Rospert, Daniel; Boyle, MD, Emmett; Sindhwani, MD, Puneet; Emmert, MD, Gregor (Translation: The University of Toledo Journal of Medical Sciences, 2020)
Metastatic breast cancer to the bladder is extraordinarily rare, with only 66 cases reported in the literature to date. Occasionally, metastatic breast cancer can first present itself with obstructive uropathy from a proposed retroperitoneal spread. We present a case of in which a 77 year old Caucasian female was found to have acute urinary obstruction from metastatic breast cancer to the bladder. Her breast biopsy came back invasive carcinoma with lobular features (Estrogen Receptor negative, Progesterone Receptor negative, and HER2 negative). She has symptoms of spontaneous urinary incontinence, but no gross hematuria. She had elevated Chromogranin A, Cancer Antigen (CA) 19-9, and CEA. She had a bladder biopsy which demonstrated metastatic breast carcinoma that stained GATA3, GCDFP15, BerEp4 positive and CK20 negative. 0% of tumor cells were positive for PD-L1 expression. The patient had renal deterioration despite bilateral ureteral stent placement, and thus required percutaneous nephrostomy tube placement. She died 4 months after her initial diagnosis.